The application of peroxidase mimetic nanozymes in cancer diagnosis and therapy - Moradi Hasan-Abad, Amin; Shabankare, Atefe; Atapour, Amir; Hamidi, Gholam Ali; Salami Zavareh, Mahmoud; Sobhani-Nasab, Ali (Frontiers in Pharmacology, 2024)
In recent decades, scholarly investigations have predominantly centered on nanomaterials possessing enzyme-like characteristics, commonly referred to as nanozymes. These nanozymes have emerged as viable substitutes for natural enzymes, offering simplicity, stability, and superior performance across various applications. Inorganic nanoparticles have been extensively employed in the emulation of enzymatic activity found in natural systems. Nanoparticles have shown a strong ability to mimic a number of enzyme-like functions. These systems have made a lot of progress thanks to the huge growth in nanotechnology research and the unique properties of nanomaterials.Our presentation will center on the kinetics, processes, and applications of peroxidase-like nanozymes. In this discourse, we will explore the various characteristics that exert an influence on the catalytic activity of nanozymes, with a particular emphasis on the prevailing problems and prospective consequences. This paper presents a thorough examination of the latest advancements achieved in the domain of peroxidase mimetic nanozymes in the context of cancer diagnosis and treatment. The primary focus is on their use in catalytic cancer therapy, alongside chemotherapy, phototherapy, sonodynamic therapy, radiation, and immunotherapy. The primary objective of this work is to offer theoretical and technical assistance for the prospective advancement of anticancer medications based on nanozymes. Moreover, it is anticipated that this will foster the investigation of novel therapeutic strategies aimed at achieving efficacious tumor therapy.